Aplicabilidade dos métodos de determinação de perfis da superfície livre em escoamentos através de condutos circulares - Costa, Helder Gomes Pinho da (1982)
This work, initially, presents some qualitative aspects of free surface flow through circular conduits. Following, some methods for determination of longitudinal profiles of the water surface to gradually varied flow are described. These methods are the Direct Step, Keifer and Chu, Keifer and Chu modified, Angles, Critical Slope, Graphical Integration and the Ven Te Chow one. That description is based on the analysis of the theoretical structure of each method, and then, the respective methodologies are used in situations of flow previously chosen. The applicability of each method is talked over and criticized in order to recommend the choice of the appropriated methodology for the different pratical situations.